2009
DOI: 10.1002/chp.20025
|View full text |Cite
|
Sign up to set email alerts
|

Promoting free online CME for intimate partner violence: What works at what cost?

Abstract: Promoting online CME, even well-received free CME, to busy community physicians requires resources, in this case at least $75 per physician reached. The effective use of promotional resources needs to be considered when developing social marketing strategies to improve community physician practices. Organizations with an interest in promoting online training might consider the use of e-promotion techniques along with conventional promotion strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
6
1
1
Order By: Relevance
“…Two recent studies demonstrated that interactive tutorials and online continuing education seminars specific to this topic may provide new methods for consolidating these educational concepts and providing mechanisms and processes for generating and answering student questions and concerns 17 , 18 . Although most students in our study indicated they would be willing to participate in additional courses and felt comfortable participating in some form of IPV intervention, these percentages did not change significantly following the educational session.…”
Section: Discussioncontrasting
confidence: 53%
“…Two recent studies demonstrated that interactive tutorials and online continuing education seminars specific to this topic may provide new methods for consolidating these educational concepts and providing mechanisms and processes for generating and answering student questions and concerns 17 , 18 . Although most students in our study indicated they would be willing to participate in additional courses and felt comfortable participating in some form of IPV intervention, these percentages did not change significantly following the educational session.…”
Section: Discussioncontrasting
confidence: 53%
“…Physician surveys show that most physicians still prefer CME delivered by traditional sources. [2][3][4] Such data suggest that online CME is in an early phase of adoption and growing slowly. In contrast, commonly cited data from the Accreditation Coun-cil for Continuing Medical Education~ACCME!…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen social marketing interventions (10%) were focused on addressing environmental issues – specifically littering. Only five programs (3%) addressed social issues, including domestic violence (Short et al , 2006; Harris et al , 2009), bullying (Bryn, 2011), road safety (Majdzadeh et al , 2011) and workplace injuries (Shams and Shamsi, 2013). Geographically, the majority of social marketing programs were implemented in the USA (58%, n = 101), followed by the UK (10%, n = 18), Australia (9%, n = 15), Canada (3%, n = 5), Iran (3%, n = 5), New Zealand (3%, n = 5), the Netherlands (2%, n = 3) and France, Germany and India had just two interventions each (1%).…”
Section: Resultsmentioning
confidence: 99%